EXPERIMENTAL STUDIES TO EVALUATE THE HEMOSTATIC EFFECTIVENESS OF HEMOBEN GEL IN RUPTURES OF THE GASTRIC MUCOSA - Erniyazov Erniyaz Azimovich (Scholar Express Journals, 2023)
Mallory-Weiss syndrome is a linear rupture of the mucous membrane in the area of the gastrointestinal junction. The main objective of this study was an experimental assessment of the hemostatic effect of submucosal administration of Hemoben gel. Taking into account the main task of the dissertation, the primary study was aimed at assessing the effect of Hemoben gel on the gastric mucosa in experimental animals. In the second series of experiments, a wound of the mucous membrane of the esophageal-gastric junction was formed by gastrotomic access. In this part of the experiment, the possibility of stopping bleeding using a gel from the drug Hemoben was tested. The advantage of introducing Hemoben gel is to achieve closure of the edges of the mucosal defect, which lasts for a long time.
Keywords: Mallory-Weiss syndrome; Hemoben Gel; hemostatic effect; mucosal defect